Organometallic Osmium Compounds in Cancer Therapy - A. Mohamed Sikkander; Rajeev Ranjan; A. Mohamed Sikkander (International Journal of Advance in Molecular Engineering, 2024)
The exploration of organometallic complexes with osmium as potential anticancer agents was indeed an area of ongoing research. These complexes were being investigated for their unique properties and mechanisms of action against cancer cells. However, it’s essential to note that the field of scientific research is dynamic, and new findings may have emerged since then. Organometallic complexes with osmium can be designed to exhibit specific features that make them promising candidates for anticancer applications. These features may include the ability to interact with cellular components, induce DNA damage, or modulate specific pathways crucial for cancer cell survival. To get the most current and accurate information on the latest developments in this field, I recommend checking recent scientific literature, research articles, and updates from reputable sources. Researchers often publish their findings in peer-reviewed journals, and these publications provide valuable insights into the progress of studies involving osmium-based organometallic complexes in cancer research and treatment. KP1339, also known as tetrachloride (dimethyl sulfoxide) (1H-indazole) ruthenate (III), is an osmium (III) compound that has been studied for its potential anticancer properties. It belongs to the class of organometallic compounds and has been investigated for its ability to induce cancer cell death and inhibit tumor growth. Osmium (II) arene complexes are a class of organometallic compounds that involve osmium in the +2-oxidation state coordinated with arene ligands. The structural characteristics and coordination environment of osmium (II) arene complexes make them interesting subjects of study for their potential applications, particularly in the field of medicinal chemistry and cancer research.
Keywords: Cancer cell replication; Cellular proteins; Induction of oxidative stress; Osmium (II) arene complexes; Osmium (III) compound